Control scheme of nonadiabatic transitions with the dynamical shift of potential curve crossing - Scheit, Simona; Arasaki, Yasuki; Takatsuka, Kazuo (The journal of chemical physics, 2014)
We investigate how the nuclear dynamics at an avoided crossing is affected and can be controlled by the introduction of a laser field whose cycle is comparable to the time-scale of the nuclear dynamics. By introducing the concepts of light-induced effective potential energy curves and dynamical avoided crossing, we describe the laser controlled nuclear dynamics and present basic control scenarios, giving a detailed explanation of the underlying dynamical mechanisms. The scenarios presented allow for examples to understand from a different perspective the results of dynamic Stark control experiments. The proposed interpretation is applied to the laser-controlled nonadiabatic dynamics between the two lowest 1Σ+ states of LiF, where the usefulness of the concepts developed is elucidated.